Estimating Entrance Fee of Sendang Gile Water Fall for State Based Recreation - Hendarto, Kresno Agus; Al Hasan, Rubangi; Yumantoko, Yumantoko; Nur, Ahmad (Jurnal Ekonomi Kuantitatif Terapan, 2018)
The government decision to increase entrance fee in tourist locations has occasionally resulted in protests among the public and tourism operators. The objective of the study, with the context at Sendang Gile water fall, is to estimate the function of recreation demand and estimate the entrance fee acceptable by the visitors. Travel cost method was used in the study. Data of visitors to the tourist destination was collected by purposive sampling method.  Results of the study showed that entrance fee increase is acceptable but at the rate lower than that determined in the Government Regulation.
Keywords: Travel cost methods; consumer surplus; Sendang Gile Water Fall